La pintura como medio expresivo para prevenir el uso de las drogas en artistas - Cruz Arias, María José (Machala : Universidad Técnica de Machala, 2019)
Painting as an expressive means to prevent the use of drugs in artists The following research work aims to raise awareness among future artists through this expressive medium, such as painting, in order to prevent the use of drugs. And be able to understand that creativity should not be wasted if not knowing how to take advantage of it. If we talk about creativity it is said that it is a capacity that people have which they have to develop an idea or create them from other associated knowledge. So he says (PONTI, 2014), "It is true that many creatives, to inspire themselves, have resorted to several substances such as alcohol, marijuana, ..., etc. It does not make sense that, every time they pretend to be creative they have to do without the drugs that, indeed, can have highly undesirable side effects "this means that the extreme abuse of drugs can have its consequences as is death.
The level of understanding and verbal expression of the child is decisive for their personal development, their social integration and, of course, their school success. Language is the best way for the child to "learn to learn". Pronunciation problems is one of the most common language disorders in children, the best known and easiest to identify. It usually occurs between three and five years, with alterations in the articulation of phonemes. In early education children do not have a writing system that allows them to express themselves, but they have an important resource that is oral language. Detecting problems in pronunciation is key to being able to intervene on time, deriving it to professionals in phonology, being the teacher the person who can detect pronunciation disorders. Initial education is marked by important changes that occur in the physical, emotional, intellectual, as well as the skills to communicate, relate, move, reason when they are in contact with the environment. This educational moment children learn at all times while they play, explore, manipulate and interact in various ways with their physical and social environment. Where the oral language is a fundamental part for La pintura como medio expresivo para prevenir el uso de las drogas en artistas El siguiente trabajo de investigación, trata de concientizar a los futuros artistas a través de este medio expresivo como lo es la pintura, para así poder prevenir el uso de las drogas. Y poder entender que la creatividad no se debe desperdiciar si no saberla aprovechar. Si hablamos de creatividad se dice que es una capacidad que poseen las personas la cual tienen para desarrollar una idea o crearlas a partir de otros conocimientos asociados. Así lo afirma (PONTI, 2014), “Es cierto que muchos creativos, para inspirarse, han recurrido a varias sustancias como: alcohol, marihuana,…, etc. No tiene sentido que, cada vez que pretendan ser creativos tengan que prescindir de las drogas que, ciertamente, pueden llegar a tener efectos secundarios altamente indeseables” esto quiere decir que el extremo abuso de las drogas puede tener sus consecuencias como lo es la muerte.
Keywords: PINTURA; CREATIVIDAD; DROGA; PROBLEMA SOCIAL